Community knowledge, perceptions and practices around COVID-19 in Sierra Leone: a nationwide, cross-sectional survey. Issue 9 (17th September 2020) - Sengeh, Paul; Jalloh, Mohammad B; Webber, Nance; Ngobeh, Ibrahim; Samba, Thomas; Thomas, Harold; Nordenstedt, Helena; Winters, Maike
Abstract : Objectives: To assess the public's knowledge, attitudes and practices about the novel coronavirus in Sierra Leone to inform an evidence-based communication strategy around COVID-19. Design: Nationwide, cross-sectional Knowledge, Attitudes and Practices survey. Setting: 56 randomly selected communities in all 14 districts in Sierra Leone. Participants: 1253 adults aged 18 years and older of which 52% were men. Main outcome measures: We calculated proportions of core indicators (awareness, knowledge, risk perception, practices). A composite variable for knowledge (based on seven variables) was created, and categorised into low (0–2 correct), medium (3–4) and high (5–7). Predictors of knowledge were analysed with multilevel ordinal regression models. Associations between information sources, knowledge and two practices (washing hands with soap and avoiding crowds) were analysed using multilevel logistic regression models. Results: We found that 75% of the respondents felt at moderate or great risk of contracting coronavirus. A majority (70%) of women did not know you can survive COVID-19, compared with 61% of men. 60% of men and 54% of women had already taken action to avoid infection with the coronavirus, mostly washing hands with soap and water (87%). Radio (73%) was the most used source for COVID-19 information, followed by social media (39%). Having a medium or high level of knowledge was associated with higher odds of washing hands with soap (medium knowledge: adjusted OR (AOR) 2.1, 95% CI 1.0 to 4.4; high knowledge: AOR 4.6, 95% CI 2.1 to 10.2) and avoiding crowds (medium knowledge: AOR 2.0, 95% CI 1.1 to 3.6; high knowledge: AOR 2.3, 95% CI 1.2 to 4.3). Conclusions: This study shows that in the context of COVID-19 in Sierra Leone, there is a strong association between knowledge and practices. Because the knowledge gap differs between genders, regions, educational levels and age, it is important that messages are specifically targeted to these core audiences.